Performance of classification criteria for gout in early and established disease. Issue 1 (28th October 2014) - Taylor, William J; Fransen, Jaap; Dalbeth, Nicola; Neogi, Tuhina; Schumacher, H Ralph; Brown, Melanie; Louthrenoo, Worawit; Vazquez-Mellado, Janitzia; Eliseev, Maxim; McCarthy, Geraldine; Stamp, Lisa K; Perez-Ruiz, Fernando; et al.
Abstract : Objectives: To compare the sensitivity and specificity of different classification criteria for gout in early and established disease. Methods: This was a cross-sectional study of consecutive rheumatology clinic patients with joint swelling in which gout was defined by presence or absence of monosodium urate crystals as observed by a certified examiner at presentation. Early disease was defined as patient-reported onset of symptoms of 2 years or less. Results: Data from 983 patients were collected and gout was present in 509 (52%). Early disease was present in 144 gout cases and 228 non-cases. Sensitivity across criteria was better in established disease (95.3% vs 84.1%, p<0.001) and specificity was better in early disease (79.9% vs 52.5%, p<0.001). The overall best performing clinical criteria were the Rome criteria with sensitivity/specificity in early and established disease of 60.3%/84.4% and 86.4%/63.6%. Criteria not requiring synovial fluid analysis had sensitivity and specificity of less than 80% in early and established disease. Conclusions: Existing classification criteria for gout have sensitivity of over 80% in early and established disease but currently available criteria that do not require synovial fluid analysis have inadequate specificity especially later in the disease. Classification criteria for gout with better specificity are required, although the findings should be cautiously applied to non-rheumatology clinic populations.